PENGUATAN KOMPETENSI MENGAJAR GURU DALAM MEMBUAT INOVASI PEMBELAJARAN BLANDED LEARNING DI SMP MUHAMMADIYAH 14 LAMONGAN - Endang Sholihatin; Gendut Sukarno; Arista Pratama; Indrawati Yuhertiana; Sukirmiyadi Sukirmiyadi; Nanang Haryono (Jurnal Layanan Masyarakat (Journal of Public Services), 2021)
AbstractThe face-to-face school learning process in the midst of the covid pandemic is carried out online. This is based on the policy of the Ministry of Education, Circular Letter Number 4 of 2020 regarding the implementation of education policies in the emergency period of the spread of the corona virus. The pandemic condition with the online learning process requires schools and teachers to innovate in the teaching and learning process. With the aim of strengthening the teaching competence of teachers in making learning innovations, the community partnership program is carried out based on special problems faced by partners of SMP Muhammadiyah 14 Lamongan, namely: (a) not being able to innovate blended learning models for online learning; (b) has not been able to optimally use e-learning based on cloud computing; (c) have not been able to innovate in making ICT-based learning media. The solution to the problem of partner needs is answered by three strategies: (a) training in the preparation and development of blended learning models for teachers; (b) create an open-source e-learning website based on chamilo and train teachers and students to use it; (c) train teachers to make learning media based on information and communication technology.Keywords: learning innovation, blended learning, learning. AbstrakProses belajar sekolah tatap muka di tengah pandemi covid dilakukan secara daring. Hal tersebut didasarkan kebijakan Kementerian Pendidikan Surat Edaran Nomor 4 Tahun 2020 tentang pelaksanaan kebijakan pendidikan dalam masa darurat penyebaran virus corona. Kondisi pandemi dengan proses pembelajaran daring menuntut sekolah dan guru untuk berinovasi dalam proses belajar mengajar. Dengan tujuan penguatan kompetensi mengajar guru dalam membuat inovasi pembelajaran program kemitraan masyarakat dilaksanakan didasarkan permasalahan khusus yang dihadapi mitra SMP Muhammadiyah 14 Lamongan yaitu: (a) belum mampu inovasi model pembelajaran blanded learning untuk pembelajaran daring; (b) belum mampu secara optimal menggunakan e-learning berbasis cloud computing; (c) belum mampu inovasi membuat media pembelajaran berbasis TIK. Solusi masalah kebutuhan mitra dijawab dengan tiga strategi: (a) pelatihan penyusunan dan pengembangan model pembelajaran blanded learning untuk guru; (b) membuat website e-learning open source berbasis chamilo serta melatih guru dan siswa untuk menggunakannya; (c) melatih guru membuat media pembelajaran berbasis teknologi informasi dana komunikasi.Kata kunci: inovasi pembelajaran, blanded learning, pembelajaran.